PENGARUH PERLAKUAN AWAL SAMPAH ORGANIK TERHADAP PRODUKSI BIOGAS SECARA ANAEROBIC DIGESTION - Dhaniswara, Trisna Kumala; Fitri, Medya Ayunda (Journal of Research and Technology, 2017)
The biggest problem currently in Indonesia is the amount of garbage that accumulates and is not controlled anywhere, especially organic waste. There are also many methods to use waste. One of waste utilization is Biogas. Organic content contained in organic waste can be used as a substart source for anaerobic bacteria. Initial treatment of organic waste in this study used as a variable, namely chopped and blended. This initial treatment is done before it is mixed with other ingredients, ie cattle dung and water. 200% water is added to the reactor along with other variables. Temperature, pH and biogas volume were observed for 30 days. Initial treatment factor of organic waste as biogas production substand showed blend treatment with decay having higher biogas production than others, is 189.99 cm3 with a composition ratio of 50% cattle dung and 50% organic waste.